PROBLEMATIKA PEMBELAJARAN BAHASA ARAB - Nandang Sarip Hidayat (An-Nida', 2012)
Problem of learning the Arabic language is the problem of certain elements of the inhibition process of learning the Arabic language, the problem of learning the Arabic language consists of linguistic problems of governance that includes sounds / Phonetik, vocabulary, writing, morphology, syntax and semantics, the problem of non-linguistic include: socio kultural, materials, facilities, instructional media, teacher competence, interests of students, and others. The world’s attention on learning the Arabic language has been started since the 17th century and in 1947 in the England and is growing rapidly in the world to Indonesia at this time.